Aplikasi Sistem Informasi Logistik dan Perannya Dalam Menunjang Peningkatan Kinerja Ekspor (Sebuah Pemikiran Untuk PT Perkebunan Nusantara X Indonesia - Kab. Jember - Nuryanto Nuryanto; Sofian Winarto (Majalah Ilmiah Bahari Jogja, 2018)
This paper was compiled based on the results of the Taruna STIMART "AMNI" Ground Practice at PT Perkebunan X Kabupaten Jember, a thought for PT Perkebunan X Jember, to use the Logistics Information System (SIL) application to support its export performance improvement, given PTP X Jember, very potential export of tobacco, especially to American and European countries. Standards and quality of export products require effective supply chain management. Agricultural commodities such as tobacco require good tobacco quality and sufficient and continuous tobacco supply. This can be achieved by utilizing the Logistics Information System. This thinking focuses on two things, namely: SIL application and improvement in export performance, based on theories, empirical and research that preceded it. The results are expected by using SIL applications, tobacco export performance carried out by PT X Regency Jember plantation is increasing.